Assessing Treatment Options of Congenitally Missing Lateral Incisors: Shall We Create or Eliminate the Space? - Acar, Ozlem; Tuncer, Duygu; Sahinoglu, Zahire; Ozcirpici, Ayça Arman; Arhun, Neslihan (The Journal of Dentists, 2014)
Maxillary lateral agenesis is one of the most seen developmental anomaly in population and requires esthetic and functional treatment from adolescence stage. Successful dental treatment is always the aim for dentists and patients, meaning that a patient’s needs are covered in an esthetic and functional way. Several dentists deal with the management of this clinical problem because a multidisciplinary approach can solve the dental demands of patients with dental agenesis. The treatment choices are; no treatment at all and accepting the space, space closure, space opening or redistribution and prosthetic replacement. There is controversy, however, about whether missing lateral incisor spaces should be orthodontically opened or closed using permanent canines to replace the missing teeth. This review considers the possible options: space maintenance and replacement of the missing tooth with denture, bridge (conventional and adhesive), or implant or orthodontic space closure with canine modification.